2022
DOI: 10.1177/02692155221121011
|View full text |Cite
|
Sign up to set email alerts
|

Elbow flexion contractures in neonatal brachial plexus palsy: A one-year comparison of dynamic orthosis and serial casting

Abstract: Objective Elbow flexion contractures are common complications of neonatal brachial plexus palsy, but evidence on how to treat these contractures is weak. This study compared the treatment of elbow flexion contractures using a dynamic orthosis or serial circular casting. Methods A randomized controlled trial was conducted with one-year follow-up. Children with an elbow flexion contracture of ≥30° were treated with either a night-worn dynamic orthosis for one year or serial casting for four weeks followed by nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Virtual reality and robotics combined to facilitate upper extremity pain management and sensory recovery after brachial plexus injury ( 44 ). The very first mention of dynamic orthoses as having a role in motor re-education came in 2018 ( 37 ), but more recent research has revealed that dynamic nocturnal orthoses are equally effective as continuous cast immobilization in treating elbow flexion contractures in kids with brachial plexus nerve birth injuries ( 45 ). As children’s upper extremities move less than those of adults, dynamic orthoses may only serve as a fixation device in children with brachial plexus injuries while offering more motor support in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality and robotics combined to facilitate upper extremity pain management and sensory recovery after brachial plexus injury ( 44 ). The very first mention of dynamic orthoses as having a role in motor re-education came in 2018 ( 37 ), but more recent research has revealed that dynamic nocturnal orthoses are equally effective as continuous cast immobilization in treating elbow flexion contractures in kids with brachial plexus nerve birth injuries ( 45 ). As children’s upper extremities move less than those of adults, dynamic orthoses may only serve as a fixation device in children with brachial plexus injuries while offering more motor support in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of development of the flexion contracture remains uncertain, but there appears to be shortening of the biceps and other elbow flexors relative to the humerus during growth (Nikolaou et al., 2011). Serial application of casts or orthoses may be helpful in preventing the development of elbow flexion contracture (Op de Coul et al., 2023). If the orthoses used to keep the elbow in extension aim to stretch the biceps muscle, it is more effective to make these in pronation.…”
Section: Advances: the Role Of Physiotherapymentioning
confidence: 99%
“…Previous studies have shown that surgical intervention is considered to be the final solution for clinical management of BPI, but it carries high risks and costs ( 5 ). In non-surgical treatments, local corticosteroid injections, splinting, and oral corticosteroids have shown significant short-term benefits but are prone to recurrence and may lead to complications such as mechanical or chemical nerve damage ( 6 ). Therefore, selecting the optimal treatment approach for BPI is crucial.…”
Section: Introductionmentioning
confidence: 99%